Analyses of worst-month rain fade statistics for Ku-band (26GHz) in the tropics - Ismail, Ahmad Fadzil; Abd Rashid, Nur Emeilin; Din, Jafri; Abdul Rahman, Tharek; Islam, Md. Rafiqul (2012)
ITU proposes that the fraction of time during which a pre-selected threshold is exceeded in the worst-month within a year is referred to as “the annual worst-month time fraction of excess”. This relates directly to situation where accumulation of outages at a specific threshold in one specific month has the worse effect on the transmission link than if compared to the accumulation that were distributed throughout the year. “Worstmonth” is basically where the threshold is exceeded for the longest time. The study of the worst-month statistics is critical to the designers of telecommunication systems since there might be cases where impairment can be dominated by a single month of the year due to local weather pattern